Variable boundary conditions for solving the problem of dispersed flow moving. Issue 1 (November 2020) - Paramonov, A; Mostovenko, L
Abstract: The paper presents comparing the results of numerical and full-scale experiments which conducted on an inertial-vacuum dust collector (IVDC). In September 2018, a full-scale experiment was held at the Omsk heat power station №4, it was allowed to verify the calculated data in ANSYS CFX. The boundary conditions were corrected after the initial calculations on IVDC of second generation. The results of numerical experiments, that conducted earlier, were corrected. In article it is spoken in detail about comparison of the dependences of the individual elements heights and their influence on the installation collection efficiency.